2021
DOI: 10.1186/s12875-021-01431-x
|View full text |Cite
|
Sign up to set email alerts
|

Can social capital play a role in contracting services of family doctors in China? Reflections based on an integrative review

Abstract: Background The family doctors’ contract service problem is not about government management alone, but an interaction of a complex social environment. Consequently, the effect of contracted services of family doctors not only depends on policy incentives but also needs to win the participation, acknowledgement, and confidence of community residents. The purpose of this integrative review is to examine whether there is any significant evidence that social capital in the form of social networking … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…One study criticized two-way referrals for transferring patients only from community health centers to hospitals but not from hospitals to community health centers. There has not been enough focus on increasing the attractiveness of community health centers, and there is an urgent need for a convenient and effective referral system [ 23 , 29 , 30 ]. It is also necessary to increase the motivation of secondary and tertiary hospitals to admit patients from community health centers.…”
Section: Discussionmentioning
confidence: 99%
“…One study criticized two-way referrals for transferring patients only from community health centers to hospitals but not from hospitals to community health centers. There has not been enough focus on increasing the attractiveness of community health centers, and there is an urgent need for a convenient and effective referral system [ 23 , 29 , 30 ]. It is also necessary to increase the motivation of secondary and tertiary hospitals to admit patients from community health centers.…”
Section: Discussionmentioning
confidence: 99%
“…The participation of social organizations in the elderly care services has become an important supplement to the elderly care system in China, bridging the shortcomings of public elderly-care and home-based care in providing adequate and high-quality elderly care services [ 4 ]. De Montigny JG pointed out in a study that multi-sector collaboration, specifically the cooperation between the government and social organizations, can enhance the quality and efficiency of social services to a certain extent, especially in the field of healthcare for older adults [ 5 , 6 ]. Previous studies had shown that organizations and communities with higher social capital were more efficient, creative and could provide better services than organizations with lower social capital [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study analyzed the factors that affect residents’ contracts with FDs from both qualitative and quantitative aspects. Yuan et al and Xu et al used qualitative research to show that the effect of implementing relevant policies, the government’s support for FDCSs and social capital affect residents’ contracts with FDs ( 18 , 19 ). Other studies have used quantitative methods and found that the reimbursement rate of medical insurance, the medical level of CHCs, the chronic disease management needs of residents, satisfaction with FDs and awareness of FDCS policies are the factors that affect residents’ contracts with FDs ( 20–24 ).…”
Section: Introductionmentioning
confidence: 99%